Learning through community service: Bangladesh perspective - Banerjee, Sanjoy (BRAC University, 2010)
This paper discusses the need to practice “Service Learning” as an effective way of learning for the university students in Bangladesh. Bangladesh is a very fertile land to practice service learning which advocates volunteer work to enhance academic experience. The volunteering university students could be both male and female and from Bengali and English medium background. The English students can tutor underprivileged children to help them write better composition in English. The science students can tutor the demanding but poor students. They can also experiment things in real life contexts. The BBA students can demonstrate classroom learning in some small and medium enterprises. Moreover, the volunteering university students can serve the humanity by creating awareness among the slum dwellers about common health problems. Besides, they can talk or stage short performances on the bad effect of drug addiction at some English and Bengali medium schools. Later on, they would do reflective writing and by this way their writing would be better gradually. The writer hopes that service learning has its prospect, validity and reliability in Bangladesh.